Tax Rate Cuts and Tax Compliance-The Laffer Curve Revisited - Papp, Tamas (IMF Working Papers; Working Paper ;, 2008)
The paper shows how tax rate cuts can increase revenues by improving tax compliance. The intuition is that tax evasion has externalities: tax evaders protect each other, because they tie down limited enforcement capacity. Thus, relatively small tax rate cuts, which decrease incentives to evade taxes, can lead to increased revenues through spillovers - creating Laffer effects. Interestingly, tax rate cuts here imply increasing effective taxes. The model is consistent with what happened in Russia, and may provide basis for further thinking about tax rate cuts in other countries.